Respon Imun Humoral Pada Larva Helicoverpa armigera hubner (Lepidoptera : Noctuidae) Pasca Infeksi HaNPV (Helicoverpa armigera Nuclear Polyhedrosis Virus) dan Keturunannya - Nani, Kurnia (Fakultas MIPA UNM, 2011)
NPV is one of the biological insecticides that kill the target by infecting their cells including hemocytes. Hemocytes play a key role on defense mechanism against pathogens like NPV. This defense mechanism may cause the insect to become more tolerant as well as to chemical insecticides. The tolerances of insect to NPV could be induced by humoral immune system (HIS). The HIS can be recorded by watch prophenoloxidase (PPO) activity or the presence of antibacterial compound (AC). Based on that assumption, this research was conducted to observe the alteration of PPO and AC due to sublethal infection of HaNPV (Helicoverpa armigera nuclear polyhedrosis viruses) on Helicoverpa armigera larvae and their offspring. PPO was detected as PO and measured spectrometrically on microplate-reader. Protein concentration was measured based on the color which appears due to protein-CBG (PO and Bradford reagent) bond at 570 nm. Protein concentration was calibrated with BSA. The occurrence of antibacterial activity was tested using modified Hoffman method. Inhibition zones were used to measure the antibacterial activity from E. coli (Gram negative) and B. cereus (Gram positive). Immune responses were observed on the fifth instar Helicoverpa armigera after 24 hpi by HaNPV (NPV-P) and their offspring (NPV-F1 and NPV-F2). Also, immune response on control larvae (K-P) were monitored and their filial (K-F1 and K-F2). The titer of PO enzyme were not significantly different for each generation. There was no inhibition zone on antibacterial activity test in every generation on NPV-P and K-P larvae.